Associations between sleep conditions and body composition states: results of the EPISONO study. Issue 5 (24th May 2019) - Piovezan, Ronaldo D.; Hirotsu, Camila; Moizinho, Renato; de Sá Souza, Helton; D'Almeida, Vania; Tufik, Sergio; Poyares, Dalva
Abstract: Background: Evidence suggests anthropometric indicators of obesity are associated with changes in sleep quality and quantity, and the presence of obstructive sleep apnoea (OSA). Investigations including diverse and objective evaluations of sleep and body composition are scarce. We aimed to evaluate the associations between indicators of sleep impairment and body composition states in a sample from a population‐based study. Methods: Participants of the first follow‐up of the EPISONO (São Paulo, Brazil) > 50 years were cross‐sectionally evaluated. Sleep was assessed through questionnaires, actigraphy, and polysomnography. Body composition was evaluated by bioelectrical impedance analysis. Appendicular skeletal muscle mass adjusted for body mass index defined sarcopenia (men <0.789 and women <0.512). Total body fat defined obesity (men >30% and women >40%). The overlap between both conditions defined sarcopenic obesity (SO). Final results were obtained by multinomial logistic regression analysis. Results: Three hundred fifty‐nine adults [mean (standard deviation) age, 61 (8.8) years; 212 (59.1%) female] were enrolled. Obesity was detected in 22.6% of the sample, sarcopenia in 5.6%, and SO in 16.2%. After controlling for covariates, OSA was associated with SO [odds ratio = 3.14, 95% confidence interval (CI) = 1.49–6.61]. Additionally, nocturnal hypoxaemia was associated with both obesity (adjusted odds ratio = 2.59, 95% CI = 1.49–4.49) and SO (odds ratio = 2.92, 95% CI = 1.39–6.13). Other indicators of poor sleep/sleep disorders were not associated with body composition states. Conclusions: Sarcopenic obesity but not obesity alone was associated with OSA. Both obesity and SO but not sarcopenia were associated with nocturnal hypoxaemia. The findings suggest a complex pathophysiologic relationship between adverse body composition states and OSA. Upcoming research on risk factors and therapeutic interventions for OSA should target synchronically the lean and adipose body tissues.